2012
DOI: 10.1515/hsz-2012-0204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cathepsin K deficiency on intercellular junction proteins, luminal mucus layers, and extracellular matrix constituents in the mouse colon

Abstract: Cathepsin K has been shown to exhibit antimicrobial and anti-inflammatory activities in the mouse colon. To further elucidate its role, we used Ctsk−/− mice and demonstrated that the absence of cathepsin K was accompanied by elevated protein levels of related cysteine cathepsins (cathepsins B, L, and X) in the colon. In principle, such changes could result in altered subcellular localization; however, the trafficking of cysteine cathepsins was not affected in the colon of Ctsk−/− mice. However, cathepsin K def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(86 reference statements)
0
7
1
Order By: Relevance
“…3D, 3H) or via other proteolytic enzymes (14, 48). Several lines of evidence demonstrated that deficiency of CatK (13, 14, 49) or other cathepsins (48, 50) altered the expression of other proteins. Such a role of CatK may not simply relate to its proteolytic activity, a longstanding question that has still remained unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…3D, 3H) or via other proteolytic enzymes (14, 48). Several lines of evidence demonstrated that deficiency of CatK (13, 14, 49) or other cathepsins (48, 50) altered the expression of other proteins. Such a role of CatK may not simply relate to its proteolytic activity, a longstanding question that has still remained unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main focus of research was for a long time on the ubiquitously expressed cathepsins B, D, and L. In contrast, the cysteine cathepsins K and S gained attention only more recently (Arampatzidou et al 2012;Dauth et al 2012;Driessen et al 1999;Friedrichs et al 2003;Muller et al 2014;Pierre and Mellman 1998;Tamhane et al 2014;Tepel et al 2000). This is because of their cell type-specific expression and vital functions, for instance, in the pericellular space (resorption lacuna) of osteoclasts or in the extracellular space Fig.…”
Section: Endo-lysosomal Cysteine Peptidases From a Canonical Perspectivementioning
confidence: 99%
“…An example where cysteine cathepsins cleave extracellular matrix components like collagen IV under physiological conditions at neutral pH is seen by epidermal keratinocytes which secrete cathepsin B upon mechanical scratch wounding for ECM degradation to ease keratinocyte migration for wound healing and tissue regeneration (Buth et al 2007). Another example is provided by investigations on the gastro-intestinal tract, where cysteine cathepsins resume functions in the extracellular space of the mucosa during tissue regeneration from mechanical trauma, or where cysteine cathepsins are active even at the gut lumen-exposed apical side of the mucosal wall (Arampatzidou et al 2012;Mayer et al 2009;Tamhane et al 2014;Vreemann et al 2009). A striking and well-studied example in which cysteine cathepsins are active for a prolonged time on one of their natural targets under non-favorable conditions is realized in the thyroid gland, where cathepsins B, K, L, and S process thyroglobulin differently depending on the conditions encountered (Brix et al 1996(Brix et al , 2001Tepel et al 2000;Friedrichs et al 2003; Jordans et al 2009).…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that neur aminidase I is a negative regulator of lysosomal exocyto sis, and its deficiency results in increased lysosomal exo cytosis [87]. In cathepsin K deficient mice, alterations in the architecture of colonic enterocytes and the localiza tion of E cadherin and occluding were observed [88].…”
Section: Lysosomal Storage Versus Cell Functionmentioning
confidence: 99%